The roles of leptin and LEP and LEPR gene polymorphisms in pathogenesis of breast cancer - Knuła, Hanna; Rubiś, Błażej; Rybczyńska, Maria (Contemporary Oncology/Współczesna Onkologia, 2009)
It is postulated that SNP (single nucleotide polymorphism) within LEP and LEPR genes could play a crucial role in the pathogenesis of numerous diseases including cancer. Due to the polymorphisms, the amino acid seq-uence is affected, which results in the receptor’s extracellular domain modification and LEP expression modu-lation followed by whole metabolism alteration. Consequently, the leptin-receptor binding is disturbed, leading to cells’ resistance to leptin, but on the other hand LEP gene expression can be induced. It is then suggested that any leptin-receptor interaction disorder resulting from LEP and LEPR polymor-phisms can promote carcinogenesis due to increase of the risk factor, leptin. On the other hand, they can also contribute to lowered cancer risk since those polymorphisms can decrease the ligand-receptor binding efficiency and consequently diminish signal trans-duction. Thus, the influence of leptin on multifactorial disorders such as cancers is crucial. However, this contribution requires further, detailed and extensive studies.